Endogamy in water buffaloes of Murrah dairy breed raised in Brazil - Malhado, C. H.M.; Ramos, A. A. [UNESP]; Carneiro, P. L.S.; Affonso, P. R.M.; Souza, J. C. (My University, 2010)
The goal of the present study was to analyze the endogamy of Murrah buffaloes over 5 generations in 10 Brazilian herds. Pedigree information of 5,062 animals born from 1972 on were used. The mean endogamy coefficient and the percentage of endogamic animals increased from 0.33 and 1.31% in the second generation to 2.58 and 50.17% in the sixth generation, respectively. The expected endogamy increases caused by the unbalanced contribution of founders was equal to 0.48% and the founder effective number (fe) was 103. The genetic contribution of 5, 10 and 17 most influent ancestors (founders or not) explained, in the same order, 29.5, 41.13 and 50% of the genetic variability in the whole population. The mean endogamy coefficient increased over generations, what indicates that matings among closely related individuals have been allowed. Management and breeding strategies should be implemented to reduce the endogamy in the analyzed herds.
Keywords: Genetic variability; Inbreeding; Pedigree